Chinese Culture in the Cirebon Sultanate: Symbolic and Philosophical Meanings - Mukhoyyaroh Mukhoyyaroh; Didin Saepudin; M. Ikhsan Tanggok (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University of Jakarta., 2021)
This paper aims to explore the symbolic and philosophical meaning of the elements of Chinese culture in the Kasepuhan Palace, Cirebon. In this palace, there are many Chinese cultural ornaments that adorn this historical site. One of them is the Siti Inggil building, where there are walls pasted with Chinese ceramics. The primary data of this paper were obtained from the field by means of observation, documentation, and direct interviews. Data analysis used descriptive qualitative and semiotic methods with archaeological, anthropological, and socio-historical approaches. This article confirms that the Chinese ornaments in the Cirebon Sultanate prove the process of cultural acculturation between Chinese culture and Cirebon culture. In Chinese tradition, the dragon is a symbol of the Chinese emperor. while the image of the Phoenix bird is a symbol of the female emperor, peace and prosperity, and the image of the fish is a symbol of darkness and luxury.